Eutanásia voluntária : alguns problemas bioéticos - Cruz, Wesley Torres da (2023)
This paper discusses key issues around the notion of life and possibility of its cease through euthanasia. Some of the most important philosophical debates on the theme will be explored under the aspect of practical ethics. Related issues such as bioethics and biological sciences will be addressed and their ethical implications will be discussed to contend for the permissibility of euthanasia based on philosophical and scientific research. At first, it will be presented the vision that the great media and common sense has about voluntary euthanasia and it will be questioned in its assuptions. The notions of rationality and self-consciousness as they appear in physicalist models of philosophy of mind will be key premises of our argumentation to justify the decriminalization of voluntary euthanasia and, in some cases, non-voluntary euthanasia. The main objective of this work is to present arguments that extend the discussion around the permissibility of voluntary euthanasia both in the philosophical and scientific spheres.